1995
DOI: 10.1007/bf02761895
|View full text |Cite
|
Sign up to set email alerts
|

Splenic abscess following blunt abdominal trauma

Abstract: A rare case of splenic abscess occurring after blunt abdominal trauma in a previously healthy boy is reported. The diagnosis was made by ultrasonography. The patient recovered after splenectomy and drainage of subphrenic and intraperitoneal pus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The most clinical presentation of patients with splenic abscess is a classical triad of fever, left upper quadrant pain and splenomegaly [6]. Kumar et al reported a case of splenic abscess in a healthy boy after abdominal blunt trauma who presented with fever and ultrasound detected the splenic abscess, however our patient had not had fever and ultrasound findings were not suggestive of splenic abscess [7]. Also, in our patient in the first and second ultrasound examination no increasing in size of spleen was detected.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The most clinical presentation of patients with splenic abscess is a classical triad of fever, left upper quadrant pain and splenomegaly [6]. Kumar et al reported a case of splenic abscess in a healthy boy after abdominal blunt trauma who presented with fever and ultrasound detected the splenic abscess, however our patient had not had fever and ultrasound findings were not suggestive of splenic abscess [7]. Also, in our patient in the first and second ultrasound examination no increasing in size of spleen was detected.…”
Section: Discussionmentioning
confidence: 55%
“…Percutaneous drainage has been suggested as the first line of treatment to avoid splenectomy [6]. Although multilocular abscesses, necrotic debris and illdefined cavities seems to be not responsive to percutaneous drainage and surgery intervention is necessary [6][7][8][9][10].In our patient ambiguity in the accurate detection of splenic abscess leads to early surgery intervention. Open splenectomy is a standard choice of treatment of splenic abscess with a mortality rate of 0-17%, but laparoscopic splenectomy is also a safe method in selected patients [5,6].…”
Section: Discussionmentioning
confidence: 72%
“…It is less invasive and less costly than surgery. The success of percutaneous drainage depends on the morphology and localization of the abscess . In our patient, the initial treatment with intravenous antibiotics was unsuccessful.…”
mentioning
confidence: 77%
“…The incidence of splenic abscess ranges from 0.2 to 0.7% in population‐based autopsy studies . The predisposing factors for splenic abscess include immunosuppression, diabetes mellitus, presence of infections at different primary sites, haematological disorders, malignancy and trauma . Intravenous drug users and alcoholics have shown an increased incidence in comparison with other groups .…”
mentioning
confidence: 99%
See 1 more Smart Citation